PENGARUH KREATIVITAS DAN PROFESIONALISME TERHADAP KEGIATANPEMBELAJARAN GURU IPS SEJARAH SMP DI KAB SUKOHARJO - Hariyani, Sri; Waluyo, Herman J.; Agung S., Leo (Sebelas Maret University (UNS), 2016)
The quality of education has been only in the spotlight in the eyes of our society. Professionalism and creativity of teachers considered to be a variable that has a relationship with the quality of education. The purpose of this study to analyze the level of professionalism and creativity of teachers in learning activitiesIn this study, experiments were conducted on a social studies teacher at the junior high school history Sukoharjo in the year 2011/2012. The samples in this study is done by using the all populations. The data analysis technique used is a two way analysis of variance.Results: In this study indicate that: 1) there was no significant effect on the level of creativity of learning activities on social studies teacher of History in Sukoharjo; 2) there is a significant effect on the activity level of professionalism of teachers teaching in social studies teachers in the history of Sukoharjo year 2011/2012; 3) there was no significant effect of the interaction level of creativity and professionalism of teachers on learning activities History Social Studies teacher in Sukoharjo 2011 / 2012.Implikasi this study by its level of creativity and professionalism can improve the learning activities in a social studies teacher of History. Thus the learning achievement History IPS can be improved through enhanced learning activities organized by the teacher.